Seroprevalence of Syphilis among Iraq’s Blood Donors and Their Relation with Blood Group and Rh Factor - Suad Azeez Hassan1 , Eman S. Nassir2 , Aseel I. Ibrahim1 , Luma Tareq3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim of Study: to detect the frequency of syphilis disease among healthy blood donors and if there’sassociation with ABO Blood groups and Rh factor.Methods and Material: this study performed in Iraq National Blood transfusion in Baghdad city, collection ofblood samples obtained from apparently healthy blood donors for a 12 month period (Jan.2018 toDec.2018).Blood group for the volunteers was determined by forward and revers grouping method. Detection ofsyphilis performed by using ELISA technique (fortress,BXE0995C, united Kingdom) for detect antibodiesin the human serum. Syphilis test on of the routine test applied in the blood donor bank in Iraq.Result: a total of 178966 healthy volunteers included in the study, all were blood donors, age 18-60 years,with mean age of 39 years. Only 1233 (0.69%) appeared infected with syphilis, 1208 (98%) were males while25(2%) were females; 444(36%) seropositive was blood group A, while blood group O and blood group Bseropositivity was 366(29.7%) , 333(37%) respectively, The lowest percentage recorded for blood group ABat 90(7.3%). The prevalence of syphilis with Rh factor was as following: 1147(93%) of seropositive was Rh+ve whereas 86(7%) was Rh -ve. Conclusion: blood group A and O are the most prominent blood groupsamong voluntary donors and the prevalence of syphilis is equal compared with other countries.